Strategi Meningkatkan Kepuasan Pengunjung Obyek Wisata Bukit Cinta Banyubiru Kabupaten Semarang - Samtono, Samtono; Ardi, Rudi Prasetyo (Sekolah Tinggi Pariwisata AMPTA, 2021)
The tourist attraction of Bukit Cinta is managed by the local government of the Semarang Regency. The purpose of this study is to describe the efforts made by the manager in increasing the satisfaction of visitors to Bukit Cinta tourism objects and to explain the strategies carried out by the managers in order to increase the number of visitors to Bukit Cinta tourism objects. The method used is a qualitative descriptive approach by conducting in-depth interviews with managers, employees, customers, communities, and food stall owners. The EFAS and IFAS techniques were also used and then calculated by calculating the AFE and IFE. The results showed that based on the SWOT courtesies diagram it was in quadrant 1, meaning that it